César Vallejo and Abraham Valdelomar: An encounter and poetry - Silva-Santisteban, Ricardo (2022)
When César Vallejo moved to Lima at the end of 1917, he established a fruitful personal as well as literary relationship with Abraham Valdelomar, another famous writer who had published extensively in the periodicals of the time and in some books. Valdelomar was also a poet, and his mature poetry anticipates, in a certain way, the rural and domestic tonality of Vallejo’s more developed early poems. The fraternal friendship between the two writers did not end there; Valdelomar also influenced Vallejo’s poetry, which from that point onwards away from modernism.